Development of Halal Tourism Destinations on Lombok Island in Six Features Perspective of Jasser Auda’s Maqasid Syari’ah - Alvien Septian Haerisma; Syamsul Anwar; Aziz Muslim (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2023)
This study aims to reveal how the implementation of the development of halal tourism destinations on the island of Lombok, Nusa Tenggara Barat (NTB). Researchers used parameters maqasid syari’ah of Jasser Auda to measure whether the goals can be achieved. This qualitative research applied case studies because the research object was limited to the island of Lombok. This study concluded that the motive for developing halal tourism destinations was a negative perception about tourism among Muslims in Lombok-NTB. The implementation of halal tourism development that complies with Sharia values was apparent in 4 components: attractions, accessibility, facilities, and support services. In this respect, a new perspective of maqasid al-syari’ah offered by Jasser Auda can be applied to improve people's welfare towards maslahah.